Genome Sequence Analysis of CsRV1: A Pathogenic Reovirus that Infects the Blue Crab Callinectes sapidus Across Its Trans-Hemispheric Range - Flowers, Emily M.; Bachvaroff, Tsvetan R.; Warg, Janet V.; Neill, John D.; Killian, Mary L.; Vinagre, Anapaula S.; Brown, Shanai; Almeida, Andréa Santos e; Schott, Eric J. (Frontiers in Microbiology, 2016)
The blue crab, Callinectes sapidus Rathbun, 1896, which is a commercially important trophic link in coastal ecosystems of the western Atlantic, is infected in both North and South America by C. sapidus Reovirus 1 (CsRV1), a double stranded RNA virus. The 12 genome segments of a North American strain of CsRV1 were sequenced using Ion Torrent technology. Putative functions could be assigned for 3 of the 13 proteins encoded in the genome, based on their similarity to proteins encoded in other reovirus genomes. Comparison of the CsRV1 RNA-dependent RNA polymerase (RdRP) sequence to genomes of other crab-infecting reoviruses shows that it is similar to the mud crab reovirus found in Scylla serrata and WX-2012 in Eriocheir sinensis, Chinese mitten crab, and supports the idea that there is a distinct “Crabreo” genus, different from Seadornavirus and Cardoreovirus, the two closest genera in the Reoviridae. A region of 98% nucleotide sequence identity between CsRV1 and the only available sequence of the P virus of Macropipus depurator suggests that these two viruses may be closely related. An 860 nucleotide region of the CsRV1 RdRP gene was amplified and sequenced from 15 infected crabs collected from across the geographic range of C. sapidus. Pairwise analysis of predicted protein sequences shows that CsRV1 strains in Brazil can be distinguished from those in North America based on conserved residues in this gene. The sequencing, annotation, and preliminary population metrics of the genome of CsRV1 should facilitate additional studies in diverse disciplines, including structure-function relationships of reovirus proteins, investigations into the evolution of the Reoviridae, and biogeographic research on the connectivity of C. sapidus populations across the Northern and Southern hemispheres.